An updated list of monogenoidea from marine fishes of Vietnam - Hung, Nguyen Manh; Ha, Nguyen Van; Ngo, Ha Duy (Academia Journal of Biology, 2020)
In this paper, we updated the list of monogenean species from marine fishes of Vietnam. Taxonomic position of monogenean species were arranged according to the current classification system. A total of 220 monogenean species from 152 marine fish species were listed. Distribution, hosts and references of each species were given. In addition, amendations of taxonomic status of taxa were also updated.